Extraction of Total Dyestuff from Centaury (Hypericum scabrum L.) and Dyeing of Natural Fibres under Different Conditions - MERDAN, HULYA; ERAY, FATMA; ONAL, ADEM; KAVAK, FERDA (Asian Journal of Chemistry, 2010)
In this present work, the flowers of the centaury (Hypericum scabrum L.) were extracted with distilled water. Different transition element salts were used to obtain stable and different colours with high fastness. AlK(SO4)2·12H2O, Bi(NO3)3·5H2O, CoCl2·6H2O, CuSO4·5H2O, FeSO4·7H2O, K2Cr2O7, MnSO4·7H2O, SnCl2·2H2O, ZnCl2 were used as mordant substances. According to preliminary, together and last mordanting methods, wool, silk and cotton fibres were dyed at pH 4, pH 8 and at 90 ºC, seperately. In addition, the effect of the artificial animal urine system (NH2CONH2 (3 %, m/v), NH3 (3 %, v/v), CaC2O4 (3 %, m/v)) as a mordant substance on dyeing of woollen materials was studied using together-mordanting method. The optimum dyeing conditions were determined and the results were evaluated in terms of fastness of dyed samples.